2023
DOI: 10.1101/2023.06.12.544645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting lipid nanoparticles to the blood brain barrier to ameliorate acute ischemic stroke

Abstract: After more than 100 failed drug trials for acute ischemic stroke (AIS), one of the most commonly cited reasons for the failure has been that drugs achieve very low concentrations in the at-risk penumbra. To address this problem, here we employ nanotechnology to significantly enhance drug concentration in the penumbra blood-brain barrier (BBB), whose increased permeability in AIS has long been hypothesized to kill neurons by exposing them to toxic plasma proteins. To devise drug-loaded nanocarriers targeted to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…However, they are also challenging targets for transfection ( 41 ). To achieve effective targeted delivery to macrophages, we employed an antibody conjugation strategy as previously described ( 42 ) In short, a strain-promoted alkyne azide cycloaddition (SPAAC) click chemistry method was utilized to integrate DBCO-activated F4/80 (a classical macrophage-specific marker in mice) antibody with as-prepared azide-4-O10b1-LNP (F4/80 LNP or MacLNP, Fig. 3 A ), with IgG2a-conjugated LNP (IgG LNP or Control LNP) as negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…However, they are also challenging targets for transfection ( 41 ). To achieve effective targeted delivery to macrophages, we employed an antibody conjugation strategy as previously described ( 42 ) In short, a strain-promoted alkyne azide cycloaddition (SPAAC) click chemistry method was utilized to integrate DBCO-activated F4/80 (a classical macrophage-specific marker in mice) antibody with as-prepared azide-4-O10b1-LNP (F4/80 LNP or MacLNP, Fig. 3 A ), with IgG2a-conjugated LNP (IgG LNP or Control LNP) as negative controls.…”
Section: Resultsmentioning
confidence: 99%
“… 19 More recently, it has been reported that targeting CAMs, especially VCAM, with mAbs and nanocarriers represent a promising direction for innovative stroke therapies. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our approach is represented by the lack of specificity for the ischemic region, as it occurs with DDSs equipped with antibodies against penumbra-related selective targets. 20 …”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] We can target the brain with anti-VCAM antibodies. [ 2 , 3 , 4 ] We can target T cells with a variety of markers. [ 5 , 6 , 7 ] We published last year that we could make CAR-T cells in vivo and cure a disease in a mouse.…”
Section: Dwmentioning
confidence: 99%